Relationship between Facebook usage and youth political participation: a Sub-Saharan African context - Lahabou , Mahaman; Wok, Saodah (2011)
Facebook has become one of the most popular social network sites among the youth. This social network site is intensively used on a daily basis by young people throughout the world. This study investigates the relationship between Facebook usage and youth political participation in a sub-Saharan African country (Niger). Facebook usage includes length of time on Facebook, frequency of usage, time spent daily, and number of Facebook friends. Political participation comprises political activity, political knowledge, and interest in politics. We employed Internet survey to gather data from young Nigeriens (N=139) living both inside and outside Niger. The findings indicate that intensity of Facebook use is positively related to both political activity and interest in politics but negatively related to political knowledge. There is also moderate and positive association between intensity of Facebook political groups use and political participation.